FASHIONABLE SEBAGAI SUMBER INSPIRASI DALAM KARYA SENI GRAFIS - Era wardi; Irwan Irwan (Serupa The Journal of Art Education, 2020)
The creation of this final work aims to visualize the negative impact of fashionable to be known by the public about the current trends that affect a person’s life in the from of graphic art works with serigraphy techniques. Showcasing the various negative impacts of fashionable at this time. The embodiment method of this final work goes through five stages: preparation, elaboration, synthesis, concept realization, and completion. The author succeeded in realizing 10 works with the titles: Divorces, Indifferent, Debt, Slumped, Mirror, Burden, Desire, Choice, High Heel, Present.Keywords: Fashionable, Graphic, Serygraphy